‘A racist challenge might force us apart’: divergence, reliance and empathy in Parable of the Sower, by Octavia Butler - Gabriela Bruschini Grecca (Ilha do Desterro)
This article aims to analyze racial issues in the resistance community depicted in Parable of the Sower (1993), by Octavia Butler, named ‘Acorn’. By researching the critical approaches to this novel, I observed that, as much as they admit race as a force that interferes in the relation between offenders and offended, they have not gone further in questioning how the variety and the complexity of the previous backgrounds of these racialized subjects cannot be ignored and homogenized  in the establishment of bonds among the offended as well. As I aim to demonstrate, the world experience carried by each character, determined especially by race and social class, helps meditating on their own asymmetrical positions and showing how their empathy towards one another has to be built and (re-)negotiated all the time.